Green composites from natural resources - Thakur, Vijay Kumar, 1952- (Boca Raton, Florida : CRC/Taylor & Francis, 2014)
'Global awareness of environmental issues has resulted in the emergence of economically and environmentally friendly bio-based materials free from the traditional side effects of synthetics. This book delivers an overview of the advancements made in the development of natural biorenewable resources-based materials, including processing methods and potential applications in green composites. Biorenewable polymers are a special class of natural material found in nature, such as natural fibers, wheat straw, rice husk, and saw dust. In addition to offering renewable feedstocks, natural biorenewable materials are compostable, recyclable, edible, and more energy efficient to process than plastic.Green Composites from Natural Resources covers various kinds of cellulosic biofibers, such as: hemp fibers, jute, saccaharum cilliare fibers, pine needles, grewia optiva fibers, sisal fibers, eulaliopsis binata flax fibers, coconut fibers, eulaliopsis binata baggase fibers, rice husk, saw dust, wood, flour, straw. With scopes for the utilization of natural resources-based materials as potential replacements for traditional petroleum feedstocks on the rise, more scientists and researchers are exploring new composite materials based on biorenewable resources. This book provides information on more eco-friendly and sustainable alternatives to synthetic polymers and discusses the present state and growing utility of green materials from natural resources'--
Includes bibliographical references and index.
Keywords: Polymeric composites; Fibrous composites; Biopolymers; Cellulose fibers; Polymeric composites -- Environmental aspects